Order, Disobedience and Power in Kieslowski’s Dekalog - Barış, Janet (CINEJ cinema journal, 2018)
The Dekalog series, comprised of ten films made by Kieslowski in 1989-90 for the Polish TV, inspired by the Ten Commandments (Decalogues) in the Torah, treats the goodness and innocence of human beings, as well as the evilness and anxiety. Generally, as a common element in all films of the series, appears the triangle of order-submission-disobedience and the power field becomes a tide moving back and forth between different characters. According to Foucault, power is perceived differently today, compared to the past. In the earlier times, power was perceived to be the rulership of a king over its subjects, while today, different types of power exist. Foucault argues that the punishment directed towards the body before is now directed to the soul. The discourse in the Ten Commandments that directs people what to do and what not overlaps the Foucauldian definition of power and the punishment of the soul. This phenomenon appears in every film of the series differently, through the characters and the plot. This article’s objective is to examine Kieslowski’s Dekalog series through the relationship between order, submission and power, and to discuss the effects of this relationship over the characters.